Hygienic Problem of Environmental Pollution by Waste of Animal and Poultry Complexes - Kosimov, Kh.; Ibrokhimov , K. I. (International Journal of Membrane Science and Technology, 2023)
The article presents digital material illustrating the sanitary and hygienic problem that arose as a result of environmental pollution (atmospheric air, water, soil) with livestock and poultry waste due to imperfect technology for keeping farm animals (ventilation system, optimization of the microclimate and disposal of solid and liquid production waste). It is shown how much and what waste products are excreted by farm animals (poultry, pigs, cattle) during different periods of ontogenesis and what volumes of them, not utilized, are stored, polluting the habitat of animals and humans with substances harmful to their health (ammonia, hydrogen sulfide, urea, protein decomposition products, etc.). With manure, droppings, and wastewater, numerous pathogenic organisms enter the soil, underground and surface waters, maintaining their viability and virulence for a long time, supporting the circulation of pathogens of dangerous diseases of farm animals and humans (salmonellosis, brucellosis, tuberculosis, helminthiases, coccidiosis, and others). The large number of animals in agricultural complexes with suboptimal growing technology contributes to the spread and maintenance of various dangerous diseases that reduce the productivity and vitality of animals. The authors of the article, stating the problem, convincingly propose to move to environmentally and economically optimal technologies for raising farm animals based on modern, scientifically developed technologies of agricultural production. To optimize the microclimate of livestock premises, it is necessary to more intensively introduce methods of ionization, ozonation and the use of microorganisms that utilize waste products of farm animals and microorganisms that are antagonists to pathogens. Innovative technologies for keeping animals on a scientific basis should combine animal husbandry, soil science and crop production into a single cycle, which will minimize the circulation of pathogens in the environment and ensure environmental and food security in the Republic of Uzbekistan.